Occupational alienation among women working in the reeducation centers - for girls - of Constantine - Bengouache, Khaled; Layeb, Rabah (Journal of Human Sciences, 2023)
The study aims to identify the level of professional alienation, and its most important manifestations among the working woman in the Girls Re-education Center in Constantine. The descriptive approach was used in this study, and the scale of alienation (Melvin Seaman 1959) was applied to measure the phenomenon on a sample of 38 workers who have direct contact in their daily work. The study founded a high degree of professional alienation among women working in the Re-education Center. The dominant manifestation was a feeling of helplessness among female workers, while the educational level had no statistical indication of professional degree alienation among them.